Risk level of firefighters' activities in DKI Jakarta province: a study of occupational safety and health (OSH) - Suci Puspita Sari (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Fire disasters pose risks to the community but also to firefighters. In dealing with a fire disaster, officers sometimes have to be faced with events that are detrimental to them. The purpose of this study is to carry out a hazard risk assessment and provide suggestions for controlling the hazards faced by firefighters. The research method used is qualitative with a descriptive study design approach, through in-depth interviews and direct observation. The results of the study indicate that there are potential hazards faced by firefighters starting from preparation activities, going to the location of the fire incident to returning to the post. The amount of risk faced is dominated by medium risk, for high risk it occurs during the extinguishing process, and for low risk only when officials receive news of a fire disaster. For risk reduction efforts, the forms of control that can be implemented can be in the form of engineering engineering, administrative controls, and Personal Protective Equipment.